2017
DOI: 10.18869/acadpub.jpcp.5.3.177
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Training of Life Skills on Social Skills of High School Students With Intellectual Disabilities

Abstract: Objective:In this study, we planned to investigate the effectiveness of life skills training on the social skills of students with intellectual disabilities. Methods:In this experimental study, with pretest and posttest design and control group, an equal number of participants was randomly assigned to experimental and control group. Life skills training were provided to experimental group (n=20) in nine sessions, whereas control group was in neutral state. The teacher completed the pretest and posttest Social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
0
10
0
2
Order By: Relevance
“…However, the current trend is for students to be exposed to the general education curriculum, preventing students from receiving essential instruction in nonacademic areas such as social skills. The increase in scores of the social skills curriculum indicated that long-term extensive instruction could be beneficial to continue to incorporate necessary functional life skills into the curriculum of deaf students [12]. Finally, the mandate for transitional…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the current trend is for students to be exposed to the general education curriculum, preventing students from receiving essential instruction in nonacademic areas such as social skills. The increase in scores of the social skills curriculum indicated that long-term extensive instruction could be beneficial to continue to incorporate necessary functional life skills into the curriculum of deaf students [12]. Finally, the mandate for transitional…”
Section: Discussionmentioning
confidence: 99%
“…Social skills can be defined as skills that allow each child to interact with others successfully. Sometimes individuals with a disability have behaviors that are unacceptable in social relationships [12]. The inappropriate social skills can be a characteristic of their disability.…”
Section: Introductionmentioning
confidence: 99%
“…Araştırma sonuçlarına göre deney grubunda yer alan çocukların eğitimin etkisine bağlı olarak sosyal uyum ve sosyal yaşam düzeylerinde kontrol grubundaki çocuklara oranla anlamlı bir farklılaşma görülmektedir. Behroz-Sarcheshmeh, Karimi, Mahmoudi, Shaghaghi, ve Jalil-Abkenar (2017) zihinsel yetersizliği bulunan lise öğrencilerine yönelik uyguladıkları yaşam becerileri eğitim programının öğrencilerin işbirliği ve öz-kontrol gibi sosyal becerilerine olumlu etki ettiği sonucuna ulaşmışlardır. Behroz-Sarcheshmeh ve diğerleri (2017)'nin, öğrencilerin, yaşam becerileri eğitim programıyla eğitim sürecinin dışında kalan zamanlarda da desteklenmesini vurguladıkları çalışmada elde ettikleri bulgular, yaşam becerilerinin çocukların hayatının her alanında desteklenmesi gereken beceriler olduğu düşüncesini pekiştirebilen bir sonuç olarak gösterilebilir.…”
Section: Sonuç Ve Tartışmaunclassified
“…At the same time, specific life skills consist of academic skills, intellectual skills, and vocational skills. Personal skills consist of self-awareness and rational thinking [48]. Self-awareness is more focused on the ability of students to reflect on themselves in the family environment, habits, hobbies, and others.…”
Section: Why Outdoor Education?mentioning
confidence: 99%